The career competencies of self-initiated and assigned expatriates: assessing the development of career capital over time - Dickmann, Michael; Suutari, Vesa; Brewster, Chris; Mäkelä, Liisa; Tanskanen, Jussi; Tornikoski, Christelle (Taylor and Francis, 2016)
Building on a modern careers approach, we assess the effects of working abroad on individuals’ career capital. Given the dearth of longitudinal studies, we return to a sample of economics graduates in Finland eight years later. We measure changes in three dimensions of career capital; ‘knowing how’, ‘knowing whom’, ‘knowing why’ and find that company assigned expatriates learn more than self-initiated expatriates. All three career capital areas benefit from international experience and all are increasingly valued over time. Based on our findings, we conclude that a dynamic notion of career capital acquisition and use is needed. Managerial implications include the need for a wider view of talent management for international businesses.
Keywords: Career capital; expatriation; international careers; longitudinal studies; self-initiated expatriation